Pengaruh Pemberian Informasi Obat Terhadap Tingkat Pengetahuan Penggunaan Antibiotik Pada Pasien Di Puskesmas Belimbing Kota Padang - Nadira Atiqah Ricardo; Helmice Afriyeni; Rahmi Yosmar; Rosiana Rizal (CV. ITTC INDONESIA, 2024)
Antibiotics are drugs that function to prevent and treat infections caused by bacteria. Antibiotics given to patients irrationally can cause resistance. Antibiotic resistance is a condition where the body becomes resistant to antibiotics. Inappropriate use of antibiotics is influenced by several factors, such as knowledge problems. One of the efforts in improving knowledge about the use of antibiotics is by providing information. Providing drug information is part of pharmaceutical services that include the selection, use, determination of drugs, and how to administer the right drugs. The purpose of this study was to determine the knowledge of patients in the use of antibiotics before and after providing information and whether there is a significant influence between the provision of information on the level of knowledge. This study is descriptive with accidental sampling method using pretest and posttes design. The instrument used was a questionnaire, then the results were analyzed using chi square test analysis. In this study, the level of knowledge of respondents after being given information about the use of antibiotics at the highest percentage was in the less category (73.2%) and after being given information was in the good category (99.9%). There was no significant influence between the level of knowledge of respondents before and after giving information about antibiotics with a p value of 0.161.